Perjanjian Kerja Laut (PKL) bagi Crew Kapal Harbour Tug PT. Waruna Nusa Sentana Jakarta - Hotben Marchiano Lumban Gaol; Hulman Panjaitan; Wiwik Sri Widiarty (Syntax Idea)
The Maritime Employment Agreement is the legal basis and framework that influences the professional lives and welfare of ship crew in the maritime industry. This thesis explores the form of a Maritime Work Agreement along with the legal remedies that can be taken regarding problems that occur in the Maritime Work Agreement for Harbor Tug crew members at PT. Waruna Nusa Sentana Jakarta is a leading shipping company in Jakarta, based on the laws and regulations in force in Indonesia. This research includes an in-depth analysis of the Sea Work Agreement implemented by PT. Waruna Nusa Sentana Jakarta, with a focus on the validity of the Sea Work Agreement, the implementation of the Sea Work Agreement, obstacles in implementing the Sea Work Agreement, as well as resolving problems if disputes occur in the Sea Work Agreement in Harbor Tug ship crew PT. Waruna Nusa Sentana Jakarta. Through a mixed approach involving surveys, and document reviews, this thesis uncovers a variety of individual perspectives and experiences in maritime employment relations. The research results highlight variations in Maritime Labor Agreements implemented in these companies and their implications for crew welfare and motivation. In a broader context, this thesis also discusses the challenges and opportunities faced by shipping companies and the government in ensuring the protection of maritime workers' rights and maintaining the sustainability of the maritime industry. The findings of this research provide important insights for Harbor Tug Crew members who will join to work on board ships, for shipping companies in improving their Maritime Labor Agreements, promoting healthy working relationships, and ensuring better welfare standards for crew members and for governments. as a legal regulator in Indonesia. Thus, this thesis contributes to a better understanding of the role and impact of Maritime Work Agreements in the vital harbor tug vessel sector at PT. Waruna Nusa Sentana Jakarta and the maritime sector as a whole.